Assessment of the water footprint of the brewery industry: The case of Heineken, Addis Ababa, Ethiopia - Kumela Diro; Kenatu Angassa; Tsedekech Gebremeskel; Mikiyas Abewaa; Ashagrie Mengistu (Results in Engineering, 2024)
The brewery industry is among the most water-intensive sectors, typically consuming 4–6 L of water for every liter of beer produced, necessitating a strong focus on water sustainability. Therefore, this study aimed to quantify the water footprint (WF) of the Heineken Ethiopian beer industry in Addis Ababa (Kilinto) over five consecutive years to identify water-intensive processes and areas. A stepwise accumulative and bottom-up approach was used to measure this WF, including calculations for both the final beer product and the spent grain byproduct. In 2019 and 2020, a significant portion of water consumption was attributed to spent grain extraction. By 2023, although the blue water footprint of both products remained within sustainable limits, more water was used in producing the final beer than in extracting spent grain. This suggests rapid improvements in water efficiency within the brewery, likely driven by effective water management practices such as leak detection and the use of water-efficient equipment and processes. The WF assessments also evaluated four sections of the brewery: utility, brewing, packaging, and general services. While utility, brewing, and packaging sections demonstrated improved water efficiency over time, the general services section saw a decrease. Given that general services are the most water-intensive area, prioritizing water management strategies in this section is crucial for overall sustainability.